2022
DOI: 10.3390/app12136295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depth on Ultrasound Point Shear Wave Elastography in an Elasticity Phantom

Abstract: Background: Phantom studies are widely used to assess variability in measurements. This study aimed to assess the reliability and accuracy of point Shear Wave elastography (pSWE) measurements of an elasticity phantom. Methods: Measurements were obtained by an experienced certified clinical sonographer at three different depth levels in kPa, using a curvilinear 5-1MHz transducer of the EPIQ7 ultrasound imaging system. Results: A total of 180 pSWE measurements were obtained at three different depth levels (three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This study identified a positive correlation between depth and SWV measurements, which implies that the depth can affect the precision of SWV measurements. Phantom and clinical SWE studies investigating the effect of depth on elastography measurement have shown that depth may significantly impact the accuracy of the SWVs [ 22 24 ]. Therefore, our study showed that the depth of the pancreas was positively correlated with SWV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified a positive correlation between depth and SWV measurements, which implies that the depth can affect the precision of SWV measurements. Phantom and clinical SWE studies investigating the effect of depth on elastography measurement have shown that depth may significantly impact the accuracy of the SWVs [ 22 24 ]. Therefore, our study showed that the depth of the pancreas was positively correlated with SWV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, a total of thirteen valuable and interesting papers were published, investigating a range of novel and innovative methods, devices, and applications of ultrasound technology in industry and medicine. The papers will cover the following topics: medical diagnostics utilizing shear wave elastography (SWE) methods [1,2], photothermal and photoacoustic effects in materials [3]; shaping the frequency-response characteristics of ultrasonic transducers for use in various applications [4]; ultrasound tomography [5,6], underwater communication systems using the quadrature phase-shift keying method (QPSK) [7]; the ways in which to use standard B-mode ultrasound scanners in precise 3D imaging [8]; the use of the acoustic field beamforming (AFB) method in ultrasonic handheld scanners [9]; a system for locating and tracking objects in the air using ultrasonic detection technology [10]; the full-matrix ultrasonic non-destructive imaging of multilayer structures [11]; the Doppler ultrasound blood flow monitoring circuit system with a single element transducer [12], and the scanning of a dental implant using an intraoral high-frequency ultrasonic prototype device [13].…”
mentioning
confidence: 99%
“…Almutairi et al [1] revealed that discrepancies in the method of measuring the point shear wave elastograhy (pSWE) have been reported due to differences in the body organ, the probes used, or the sample sizes that have been examined; these could provide inaccurate findings and, therefore, affect the reliability of the diagnosis. The authors of this paper sought to assess the reliability and accuracy of pSWE measurements at a range of depths in an elasticity phantom.…”
mentioning
confidence: 99%